2022
DOI: 10.3389/fonc.2022.833719
|View full text |Cite|
|
Sign up to set email alerts
|

Hinokiflavone Inhibits Growth of Esophageal Squamous Cancer By Inducing Apoptosis via Regulation of the PI3K/AKT/mTOR Signaling Pathway

Abstract: BackgroundGlobally, esophageal cancer ranks as the seventh most common cancer. Esophageal squamous cell carcinoma (ESCC) is one of its major histological types. ESCC accounts for the vast majority of cases in China, and the mortality rate is high. Cisplatin, the standard adjuvant chemotherapy drug for ESCC, has a modest response rate due to the development of drug resistance. Hinokiflavone (HF) is a natural biflavonoid compound with anti-melanoma activity. However, its anti-tumor effect on ESCC and the underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Studies have found that many biflavones play an anti-tumor role by inducing apoptosis and/or autophagic cell death of tumor cells. For example, the biflavone Hinokiflavone suppresses the growth of esophageal squamous cell carcinoma by regulating PI3K/AKT/mTOR signal pathway to induce apoptosis [ 26 ]. Delicaflavone plays an important role in preventing NSCLC, colon cancer and cervical cancer by activating mitochondrial dependent Caspase signal pathway and inhibiting MAPK and PI3K/Akt/mTOR signal pathway [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that many biflavones play an anti-tumor role by inducing apoptosis and/or autophagic cell death of tumor cells. For example, the biflavone Hinokiflavone suppresses the growth of esophageal squamous cell carcinoma by regulating PI3K/AKT/mTOR signal pathway to induce apoptosis [ 26 ]. Delicaflavone plays an important role in preventing NSCLC, colon cancer and cervical cancer by activating mitochondrial dependent Caspase signal pathway and inhibiting MAPK and PI3K/Akt/mTOR signal pathway [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The excess dye was washed away with PBS after centrifugation. Antifade mounting medium (Beyotime, China) was added for visualization using inverted fluorescence microscope (model number: CKX31, Olympus, Japan) ( Guo et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…As an illustration, almost all C-C biflavonoids have the capacity to regulate MMPs. Hinokiflavone was found to have a similar effect, decreasing the ability of A375 and B16 melanoma cells to invade and migrate, as well as KYSE 150 cells, an esophageal squamous cell carcinoma line, by downregulating MMP-2 and MMP-9 expression [61,88]. Amentoflavone has also been discovered to inhibit invasion and migration of bladder cancer cells by reversing EMT via nuclear factor-kappa B (NF-κB) inactivation and by lowering the expression of MMP-2, MMP-9 and uPA [89].…”
Section: Inhibition Of Tumor Metastasis and Angiogenesismentioning
confidence: 98%
“…Furthermore, phosphatidylinos itol-3-kinase (PI3K) activates protein kinase B (Akt) by phosphorylating Thr308 and Ser473 (p-Akt) under normal physiological circumstances [118,119]. For example, Guo et al [88] found that hinokiflavone may lead to apoptosis in esophageal squamous cancer cells by controlling the PI3K/Akt/mTOR signaling pathway. Wang et al [120] found that amentoflavone induced apoptosis and inhibited glycolysis in glioma cells by targeting miR-124-3p.…”
Section: Induction Of Cancer Cell Apoptosismentioning
confidence: 99%